Fatty acids profile and energy content in muscle of juvenile of Peruvian rock sea bass (Paralabrax humeralis) conditioned to captivity - Rosado-Salazar, Maryandrea (2018)
The fatty acids profile and energy content in muscle of juveniles of Paralabrax humeralis conditioned at three temperatures (12, 17 and 22 °C) for a period of 90 days was evaluated. For this purpose, 2 m3 fiberglass tanks connected to water recirculation systems with temperature control were used. The fishes were fed with commercial balanced feed (pellets) of 4 mm diameter, 42% protein and 12% fat twice a day. Every 30 days the weight and length of all fishes was recorded. In addition, six fish per acclimation temperature were sacrificed to measure fatty acids concentrations and energy content of muscle tissue. The observations showed that P. humeralis quickly accepts the artificial feed reaching a 95% survival during the evaluation period. The muscle concentration of linoleic and linolenic acids increased more than 100% in the three temperature groups. Contrarily, the concentration of docosahexaenoic acid (DHA), arachidonic acid (ARA), docosapentaenoic acid (DPA) and eicosapentaenoic acid (EPA) decreased by 48, 45, 26 and 20% respectively. The energy content in muscle increased 13% during the conditioning period. It is concluded that P. humeralis adapts quickly to the conditions of captivity; however, the feed provided must contain higher amounts of ARA, EPA, DPA and DHA.